Differences in Student Learning Outcomes Using Media of Microsoft Powerpoint and Adobe Flash Player in Business Education - Abdurohim Abdurohim; Ade Risna Sari; Idam Putriyani Waruwu; Pandu Adi Cakranegara; Sarwo Eddy Wibowo (Edumaspul: Jurnal Pendidikan, 2022)
The purpose of this research is to analyze differences in student learning outcomes using media of Microsoft PowerPoint and Adobe Flash Player in business education. This research is an experimental research. In this study, there are two learning groups to be compared as research subjects, namely the learning group in the control class using Microsoft PowerPoint learning media and the learning group in the experimental class using Adobe Flash Player in business education. Both groups are given the same material. Population in this study are Private Higher Education Students in Medan City in 2022. However, because the official data for Private Higher Education Students in Medan City in 2022 is difficult to find, sample is taken randomly using snowball sampling technique. So sample in this study are 60 Private Higher Education Students in Medan City. Data analysis technique through inferential using paired t-test. The results of the study show that there are differences in student learning outcomes using the media of Microsoft PowerPoint and Adobe Flash Player in business education at Private Higher Education Students in Medan City.